Screening of anticancer activity from agarwood essential oil - Hashim, Yumi Zuhanis Has-Yun; Phirdaous, Abbas; Amid, Azura (Wolters Kluwer, 2014)
Background: Agarwood is a priceless non‑timber forest product from Aquilaria species belonging to the Thymelaeaceae family. As a result of a defence mechanism to fend off pathogens, Aquilaria species develop agarwood or resin which can be used for incense, perfumery, and traditional medicines. Evidences from ethnopharmacological practices showed that Aquilaria spp. have been traditionally used in the Ayurvedic practice and Chinese medicine to treat various diseases particularly the inflammatory‑associated diseases. There have been no reports on traditional use of agarwood towards cancer treatment. However, this is most probably due to the fact that cancer nomenclature is used in modern medicine to describe the diseases associated with unregulated cell growth in which inflammation and body pain are involved. Objective: The aim of this current study was therefore to investigate the potential anticancer properties of agarwood essential oil obtained from distillation of agarwood (resin) towards MCF‑7 breast cancer cells. Materials and Methods: The essential oil was subjected to screening assays namely cell viability, cell attachment and sulforhodamine B (SRB)‑based cytotoxicity assay to determine the IC50 value. Results: The agarwood essential oil caused reduction of the cell number in both the cell viability and attachment assay suggesting a cumulative effect of the cell killing, inhibition of the cell attachment and or causing cells to detach. The agarwood essential oil showed IC50 value of 900 μg/ml towards the cancer cells. Conclusion: The agarwood essential oil exhibited anticancer activity which supports the traditional use against the inflammatory‑associated diseases. This warrants further investigation towards the development of alternative remedy towards cancer.